“It’s Not Even Happening in Our Classes”: The Impossibilities of CRT as Racial Knowledge - Jones, Brittany; Monreal, Tim; White, Anthony (Critical Education, 2025)
Analogous to the political use of language itself in determining, even producing, student learning outcomes, the use of politically charged discourse circumscribes (the boundaries of) student learning opportunities. This ‘positive’ (i.e. productive) understanding of discourse does not only prohibit discussion about race and racism but helps determine how we can, even should, engage with issues related to race and racism. In light of both the power that discourse exerts upon students’ and teachers’ educational opportunities and the increasing racial diversity of the U.S. student population), such a development demands consideration of its potential impact on educator praxis. This paper explores how (anti-)CRT discourse contours and outlines the ‘appropriate’ teaching, discussion, and learning of race and racism within educational spaces. By examining ‘moments’ in (anti-)CRT discourse, including moments when educators push back against censorship efforts, this largely conceptual article seeks to highlight how discourse (unintentionally) produces ‘normalized’ and ‘common sense’ ways of thinking and teaching about race that get reified and (re)produced.